Evaluation of imidazolium-based ionic liquids towards vermicidal activity: in vitro & in silico studies - Charan, K. T. Prabhu; Ranjan, Prabodh; Manojkumar, Kasina; Pothanagandhi, Nellepalli; Jha, Prakash C.; Khedkar, Vijay M.; Sivaramakrishna, Akella; Vijayakrishna, Kari (RSC Advances, 2015)
A series of six different ionic liquids (ILs) of the kind 1-alkyl-3-methylimidazolium bromide/hydroxide (IL-Br and IL-OH) tailored with different N-alkyl side chains (ethyl, butyl, octyl) were synthesized and evaluated for their vermicidal activity against the Indian earthworm, Pheretima posthuma. The percentage of paralysis and mortality of earthworms against ILs were recorded in a dose dependent (at different concentrations 2, 4, 8 and 16 mM) and time dependent manner. The ILs with hydroxide as the counter anion (IL-OH) showed higher vermicidal activity compared to their bromide counterparts (IL-Br). Moreover, the ILs with the longest alkyl chain (octyl) were observed to have significant vermicidal activity compared to the rest (ethyl and butyl) as well as the standard drug, Albendazole. Furthermore, theoretical modeling was carried out to visualize the preferential docking positions of these ILs into the active site of beta-tubulin. Fascinatingly, it was found that the ILs with longest alkyl side chain showed remarkable vermicidal activity compared to the rest, and the molecular docking studies not only validated the experimental results, but also showed per-residue interaction analysis between the ILs and the different components of beta-tubulin.